Respuesta :
Answer:
The correct answer is Option C: [tex]2x-3(-3x-4)=-21[/tex]
Step-by-step explanation:
The given equations are:
[tex]y + 3x =-4\ \ \ Eqn\ 1\\2x-3y =-21\ \ \ Eqn\ 2[/tex]
The equations have to be solved using substitution method. In substitution method we find the value of a variable from one equation and put it in the other equation.
To find the value, we usually choose the equation in which a variable without any coefficient is available.
From equation 1
[tex]y +3x = -4\\y = -3x-4\\[/tex]
This value of y will be put in equation 2
[tex]2x-3(-3x-4)=-21[/tex]
It is the C option in choices
Hence,
The correct answer is Option C: [tex]2x-3(-3x-4)=-21[/tex]
Answer:
Hey, where did you get this question? Do you have answer key of this worksheets all things I need it to.
Step-by-step explanation: